1991
DOI: 10.1099/0022-1317-72-7-1497
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the 75K readthrough protein of beet necrotic yellow vein virus RNA-2 is essential for transmission by the fungus Polymyxa betae

Abstract: Two mutant strains of beet necrotic yellow vein virus (BNYVV) containing deletion mutants of RNA-2 were produced during serial passage in mechanically inoculated Tetragonia expansa leaves. The mutant strains were referred to as S-0a (RNA-1 +2a) and G-0b (RNA-1 +2b). RNA-2a and RNA-2b were about 4.3 kb and 4-2 kb in length, respectively, whereas normal sized RNA-2 was about 4.8 kb in length. In vitro translation and immunoblot analysis showed that RNA-2, RNA2a and RNA-2b all directed synthesis of the coat prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 29 publications
3
60
0
1
Order By: Relevance
“…This ORF is expressed from full-length RNA 2 by translational readthrough of the coat protein termination codon to produce the Mr ~ 75000 and M r ~ 84000 readthrough proteins of BNYVV and SBWMV, respectively (Ziegler et al, 1985;Hsu & Brakke, 1985), or by a leaky scanning mechanism in the case of P39 of PCV (E. Herzog and C. Fritsch, unpublished). There is no sequence homology between these species but the readthrough domain of BNYVV RNA 2 has been shown to be involved in vector transmission (Tamada & Kusume, 1991). Transmission of SBWMV and PCV without recourse to the fungal vector is often accompanied by deletions in the corresponding ORFs of SBWMV (Shirako & Brakke, 1984;Hsu & Brakke, 1985;Shirako & Ehara, 1986) and PCV (Manohar et al, 1993), providing circumstantial evidence for a similar role in these two viruses.…”
Section: Relationships With Other Furovirusesmentioning
confidence: 96%
“…This ORF is expressed from full-length RNA 2 by translational readthrough of the coat protein termination codon to produce the Mr ~ 75000 and M r ~ 84000 readthrough proteins of BNYVV and SBWMV, respectively (Ziegler et al, 1985;Hsu & Brakke, 1985), or by a leaky scanning mechanism in the case of P39 of PCV (E. Herzog and C. Fritsch, unpublished). There is no sequence homology between these species but the readthrough domain of BNYVV RNA 2 has been shown to be involved in vector transmission (Tamada & Kusume, 1991). Transmission of SBWMV and PCV without recourse to the fungal vector is often accompanied by deletions in the corresponding ORFs of SBWMV (Shirako & Brakke, 1984;Hsu & Brakke, 1985;Shirako & Ehara, 1986) and PCV (Manohar et al, 1993), providing circumstantial evidence for a similar role in these two viruses.…”
Section: Relationships With Other Furovirusesmentioning
confidence: 96%
“…The CP ORF has an opal translational termination codon and readthrough of this codon produces a large 84 kDa polypeptide (Hsu & Brakke, 1985). The CP readthrough domain (RT) is required for plasmodiophorid transmission of the virus (Koenig et al, 1997;Tamada & Kusume, 1991). The 39-proximal ORF of RNA2 encodes a 19 kDa polypeptide and its function is also not known.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of PCV RNA 2 indicated that the 39K protein (ORF 2) is encoded in a different frame from the coat protein gene (ORF 1) with the AUG initiation codon of ORF 2 overlapping the UGA termination codon of the coat protein gene (Manohar et al, 1993). In vitro translation experiments of PCV RNA 2 indicated that expression of the 39K protein is initiated in vitro by a leaky scanning mechanism (Herzog et al, 1995), It is believed that 39K protein may be involved in vector transmission (Manohar et al, 1993;Herzog et al, 1995) because it undergoes deletions when the virus is propagated by mechanical inoculation as does the read-through domain of the SBWMV (Shirako and Ehara, 1986;Chen et al, 1994) and that of BNYVV (Bouzoubaa et al, 1986;Tamada and Kusume, 1991). We detected 543nt deletion in read-through domain of PMTV RNA 3 and this mutated isolate (PMTV-T, Harrison and Jones, 1970) could not be acquired and transmitted by the single cystosoral culture of S. subterranea f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…In both viruses, the coat protein is encoded by the 5'-proximal gene of RNA 2 (Bouzoubaa et al, 1986;Shirako and Wilson, 1993) and the coat protein cistron is immediately followed by a long in-frame ORF which is expressed by translational read-through of the coat protein cistron termination codon to produce a read-through protein (Ziegler et al, 1985;Schmitt et al, 1992;Shirako and Wilson, 1993). In BNYVV, the read-through protein has been shown to be incorporated into virions as a minor component (Haeberle et al, 1994) and to be essential for vector transmission (Tamada and Kusume, 1991) and particle assembly (Schmitt et al, 1992). In this paper, we describe, in vitro transcription and translation of the coat protein/read-through domain of PMTV RNA 3 in a wheat germ extract system to determine if the putative leaky stop codon is suppressed during translation and to determine the frequency of this suppression event.…”
Section: Introductionmentioning
confidence: 99%